INFORMALITY AND TOTAL FACTOR PRODUCTIVITY IN KENYA - Opondo, Mary; Etyang, Martin; Ayieko, Onono (International Journal of Economics, 2022)
Purpose: The Kenyan economy is largely informal. The objective of the study was to establish the effect of size of the informal sector on total factor productivity in the country. Methodology: The study was based on the dualist theory of the economy. Data covering the period 1974 to 2016 was sourced from government publications (Economic Surveys and Statistical Abstracts), the Global Financial Development Database and the World Development Indicators. A growth accounting exercise was conducted using the Cobb-Douglas production function based on the Solow growth model. This enabled the decomposition of output growth to the contributions of labour and capital with a residual, commonly referred to as the total factor productivity which was the dependent variable in the study. The study was non-experimental and utilized a longitudinal research design using macro-level data thus limiting the possibility of data manipulation. Various theoretically and empirically recognized determinants on TFP were included as control variables. The analysis was conducted using ordinary least squares. Findings: The findings show that the size of the informal sector has a negative and statistically significant effect on total factor productivity in Kenya. Given the large informal sector, the study concluded that there is need to increase productivity of the sector in the country for improved economic performance. Unique contribution to theory, practice and policy: From the study findings, the informal sector has a negative and statistically significant effect on total factor productivity in Kenya. The study recommends the development and implementation of policies to enhance productivity in the sector. These include market and technological development, improved infrastructure and access to credit facilities.